The Achievement Test Desk Reference : A Guide to Learning Disability Identification - Flanagan, Dawn P. [et al.] (Hobboken John Wiley and Sons, 2006)
[This volume] features the most up-to-date versions of assessment instruments to measure individual achievement and learning disabilities. [In the volume, the author] offers practitioners an innovative, systematic assessment framework that applies Cattell-Horn-Carroll (CHC) cognitive theory and blends cognitive testing and response-to-Intervention (RTI) methods into one seamless process for diagnosing learning disabilities.
Include Index
Keywords: Achievement tests -- Learning disabilities